A life‐stage population model of the European sturgeon (Acipenser sturio L., 1758) in the Elbe River. Part II: assessment of the historic population decline. (25th February 2014) - Gessner, J.; Jarić, I.
Summary A post‐hoc analysis on the decline of the European sturgeon (Acipenser sturio) population in the Elbe River was performed for the end of the 19th century. A modeling approach was applied to determine the role of various factors potentially impacting the population. Using an age‐structured population model developed for European sturgeon, the estimates of fishing efficiency in the Elbe were verified. Catches reported from 1850 to 1920 were used as a basis to identify the population size, dynamics of the decline and the impacts contributing to the population decline. According to results of the model, the historic population size of the European sturgeon in the Elbe River exceeded 450 000 individuals. The population revealed a significant response in abundance of adults towards the fishery directed at spawning migrants, even at low fishery effort. Unsustainable fishery was the initial cause of the population decline, while increasing pollution and habitat degradation revealed significant impacts after 1860. The results represent a good example for the fisheries 'hyperstability' phenomenon. In the case of the Elbe fishery, an increasing fishery effort was masking the actual population decline while temporarily maintaining the overall yield. The results indicate that, for sturgeons and other species with similar life history patterns, the use of fishery data for the assessment of population dynamics and fishery sustainability has to be applied with due caution, as it might produce false images of the population size and dynamics.